Analisis Pemeliharaan Mesin Bubut Tipe C6240A di CV Karya Polyurethane - Furqonudin Furqonudin; Haris Abizar (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This The maintenance objectives of a C6240A-type lathe involve a number of crucial aspects, including gears, tool bits, toolposts, lower sled and upper sled. This study was to investigate effective maintenance strategies for each of these components, focusing on preventive and predictive maintenance. Gears: Regular lubrication is also necessary to ensure smooth gear movement and prevent excessive friction that could lead to failure. Chisel Bits: Monitoring the condition of the tool blade needs to be done regularly. Toolpost: The toolpost needs to be checked periodically to ensure availability and safety of the cutting tool. Bottom and Top Slings: Maintenance of the lower and upper slings involves checking for tension and wear. C6240A type lathe users can minimize the risk of failure, improve operational efficiency, and extend the life of the machine. The method used in this research is a qualitative method, by means of observation and interviews. The results of this study are that the gears can be more durable because lubrication is always given and not easily thirsty, the tool blade is not easily blunted because the workpiece is fed little by little, and frequent honing is done to keep it sharp. The locking toolpost is not easily damaged if you use a rubber hammer when locking, the bottom row makes a change of ashock so that it can do automatic turning. This maintenance can increase the life of the lathe for longer operation.